Ontology development for do'a and zikir Al-Ma'thur for counselling - Siti Fatimah binti Mohd Tawil
The purpose of this research was to develop an ontology for Do'a and Zikr al-Mā'thur for counselling. The ontology was constructed to provide high school counsellors with access to relevant Do'a and Zikr al-Mā'thur for counselling session and intervention. Do'a and Zikr al-Mā'thur are essential supplications towards ALLAH Azza wa Jalla, in facing challenges in life and in coping with stress. Existing search systems could not find the Do'a and Zikr al-Mā'thur that matched counselling cases. In fact, Do'a and Zikr al-Mā'thur were scattered among many sources, and even listed under different headings. The objectives of this research were to identify the methodology for ontology development for Do'a and Zikr al-Mā'thur for counselling; to develop an ontology for Do'a and Zikr al-Mā'thur for counselling, and to evaluate the ontology developed for Do'a and Zikr al-Mā'thur for counselling. The ontology development methodology was highly influenced by the methodology demonstrated by Fernandez-Lopez et al. (1997) with a close reference to Thunkijjanukij's (2009) work and Protégé practical guide by Horridge et al. (2004, 2011). The Do'a and Zikr al-Mā'thur ontology for counselling consisted of concepts extracted from supplications derived from Al-Quran and Hadith compiled by selected credible scholars, and counselling cases from the Ministry of Education, Malaysia. The ontology was built in Protégé OWL Editor Version 5. The evaluation of the ontology comprised four stages: validation and verification by two subject matter experts at the completion of the ontology conceptualization phase; following Gomez-Perez et al. (2004) and Kreider (2013) guideline and criteria; competency questions through SPARQL query testing; and users assessment on suitability of the ontology. The applied methodology has successfully developed the Do'a and Zikr al-Mā'thur ontology for counselling. The ontology consisted of 325 concepts and 303 instances with a total of 3648 axioms. Major semantic relationships were hasSupplication and isSupplicationFor. A total of 1015 Do'a and Zikr al-Mā'thur were derived from the selected credible sources and 207 counselling cases collected from three participating high schools in Gombak district. The validation and verification results included the positive endorsement and constructive judgement upon most of the ontology components. The ontology has met the criteria adopted from Gomez-Perez et al. (2004) and Kreider (2013) in terms of its comprehensiveness, consistency, extensible, ease of use and completeness. The Do'a and Zikr al-Mā'thur ontology provided correct answers to all 86 competency questions through SPARQL query testing. The ontology also yielded 83% suitable level through users assessment. Further works included the implementation of ontology concepts in ranked-output search system and its implementation as seeds for crawling on the semantic web.